Multi-walled vs. single-walled carbon nanotube dispersions in nematic liquid crystals: comparative studies of optical transmission and dielectric properties - Samoilov, A.N.; Minenko, S.S.; Fedoryako, A.P.; Lisetski, L.N.; Lebovka, N.I.; Soskin, M.S. (Functional Materials, 2014)
Comparative studies have been carried out of multi-walled and single-walled carbon nanotubes (CNT) dispersed in nematic liquid crystal matrix. Under strictly similar experimental conditions (5CB nematic host, the same supplier of CNTs, the same 50μm thick cell for optical and dielectric measurements, the same CNT concentration range, identical procedures of optical transmission vs. temperature and complex dielectric permittivity measurements), differences between single- walled and multi-walled CNTs were recorded. The most distinct differences were 3-4 times higher optical density and noticeably higher effect upon dielectric permittivity in the low-frequency range noted for single-walled CNTs, which could be clearly attributed to the difference in the specific surface area of single- and multi-walled carbon nanotubes.